2012
DOI: 10.1371/journal.pone.0040429
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 and A2: Roles in Retrograde Trafficking of Shiga Toxin

Abstract: Annexins constitute a family of calcium and membrane binding proteins. As annexin A1 and A2 have previously been linked to various membrane trafficking events, we initiated this study to investigate the role of these annexins in the uptake and intracellular transport of the bacterial Shiga toxin (Stx) and the plant toxin ricin. Once endocytosed, both toxins are retrogradely transported from endosomes to the Golgi apparatus and the endoplasmic reticulum before being targeted to the cytosol where they inhibit pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…One might speculate that if cPLA 2 a indeed is translocated at least partly to the Golgi apparatus in response to the toxin-induced Ca 2? influx, cPLA 2 a could be involved in toxin transport to and through the Golgi, as we have previously found that inhibition of cPLA 2 reduces Stx transport to the Golgi [12]. The fractionation data also show that AnxA1 is translocated to membranes upon StxB-S2 treatment, and the immunofluorescence data suggest that these membranes are at least partly late endosomal/lysosomal membranes as an increase in colocalization with LAMP1 was seen.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…One might speculate that if cPLA 2 a indeed is translocated at least partly to the Golgi apparatus in response to the toxin-induced Ca 2? influx, cPLA 2 a could be involved in toxin transport to and through the Golgi, as we have previously found that inhibition of cPLA 2 reduces Stx transport to the Golgi [12]. The fractionation data also show that AnxA1 is translocated to membranes upon StxB-S2 treatment, and the immunofluorescence data suggest that these membranes are at least partly late endosomal/lysosomal membranes as an increase in colocalization with LAMP1 was seen.…”
Section: Discussionsupporting
confidence: 65%
“…We previously showed that a modified Stx B-subunit containing two sulfation sites (StxB-S2), induced dissociation of the cPLA 2 a-AnxA1 complex [12]. To investigate whether the intact Stx, containing both Aand B-chains, would induce a similar dissociation of this complex, HeLa cells were incubated with equal molar concentrations of StxB-S2 or SLT1, an enzymatically inactive Stx mutant [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main evidence of clathrin-independent endocytosis of Shiga toxins is the formation of long surface-connected membrane tubules [33]. Toxin internalization is independent of raft-associated flotillins or scaffolding proteins like annexins, as inhibition of these two proteins in two independent experiments did not affect toxin entry [50,51]. The toxininduced activation of receptor tyrosine kinases such as Yes, Src, Syk and Lyn in different cell lines mediates the formation of clathrin coated pits to increase Shiga toxin uptake [44,52,53].…”
Section: Many Doors For Entrymentioning
confidence: 99%